Ecological Education Development Design for Middle School Students in Maintaining the Sustainability of Ujungpangkah Mangrove Essential Ecosystem Area (KEE MUP) - Nur Maulida Safitri; Rohmy Husniah; Nur Fauziyah; Riska Widiyanita Batubara; Ulfatul Ulfatul Ma’rifah; Raden Achmad Djazuli; Churun Lu'lu'il Maknun (Sasambo: Jurnal Abdimas (Journal of Community Service), 2022)
The essential ecosystem of mangroves Ujungpangkah (KEE MUP) is a protection and limited utilization area located on the coastal area in the north of Gresik Regency. This area has high biodiversity, especially various mangroves and waterbird species from different parts of the world due to their migration process. To protect this area, it is required to enhance the sensitivity of students as the young generation to react appropriately to keep the environment sustainable. In this case, education-based environmental studies (Ecological Education) is used as a sustainable approach to answering this challenge. Various activities of community services are structured through a strategic plan for ecological education implementation. With this Ecological Education, students can increase their sense of love for the environment to keep the KEE MUP conservation zone inherited sustainably